Fast and robust phase-shift estimation in two-dimensional structured illumination microscopy - Sola-Pikabea, Jorge; Garcia-Rius, Arcadi; Saavedra, Genaro; Garcia-Sucerquia, Jorge; Martínez-Corral, Manuel; Sánchez-Ortiga, Emilio (PLOS ONE, 2019)
A method of determining unknown phase-shifts between elementary images in two-dimensional Structured Illumination Microscopy (2D-SIM) is presented. The proposed method is based on the comparison of the peak intensity of spectral components. These components correspond to the inherent structured illumination spectral content and the residual component that appears from wrongly estimated phase-shifts. The estimation of the phase-shifts is carried out by finding the absolute maximum of a function defined as the normalized peak intensity difference in the Fourier domain. This task is performed by an optimization method providing a fast estimation of the phase-shift. The algorithm stability and robustness are tested for various levels of noise and contrasts of the structured illumination pattern. Furthermore, the proposed approach reduces the number of computations compared to other existing techniques. The method is supported by the theoretical calculations and validated by means of simulated and experimental results.